Interviewing Child Victims of Crime: Changes in Investigative Practices - E.G. Dozortseva; A.G. Krasavina (Культурно-историческая психология, 2017)
The article considers the problem of changes in investigative interviewing of child victims of crime in the context of a child’s social situation of development. The adult’s position in the interaction with the child is based on two principles: (1) obtaining reliable and full information about the criminal acts against the child and (2) protecting the child’s best interests. Innovations in the criminal procedural legislation concerning interviewing child victims and the possibilities of improving investigative practice are analyzed. The article also presents international experience in this sphere, focusing in particular on psychological features of different models of interviewing children. It discusses the possibilities of their adaptation and implementation in the Russian practice taking into account different cultural contexts. It is suggested that the child victim interviewing may be considered as a component of the complex medical-psychological and socio-pedagogical support for maintaining the child’s health as well as psychological and social well-being.